The political understanding of Hegel’s Greek Tragedy (2013)
The interpretation of Greek Tragedy in Hegel’s political thought helps to analyse new oppositions that have emerged in society after the incorporation of bourgeoisie as a social element that breaks with political understanding developed by modern theorist